2017
DOI: 10.1038/onc.2017.216
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of MicroRNAs mediated control of carnitine cycle in prostate cancer: molecular basis and pathophysiological consequences

Abstract: Cancer cells reprogram their metabolism to maintain both viability and uncontrolled proliferation. Although an interplay between the genetic, epigenetic and metabolic rewiring in cancer is beginning to emerge, it remains unclear how this metabolic plasticity occurs. Here, we report that in prostate cancer cells (PCCs) microRNAs (miRNAs) greatly contribute to deregulation of mitochondrial fatty acid (FA) oxidation via carnitine system modulation. We provide evidence that the downregulation of hsa-miR-124-3p, hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…Several previous studies showed that miR-378-3p was downregulated in CRC, esophageal squamous cell carcinoma and prostate cancer (27)(28)(29). In addition, miR-378-3p has been confirmed to be downregulated in CRC compared with adjacent normal colorectal tissues (28)(29)(30), consistent with the present study, and could serve as an independent prognostic marker or potential target of novel cancer therapies. The putative binding of miR-378-3p at the 3'UTR site of LBX2 further supports the hypothesis that miR-378-3p may be an upstream regulator of LBX2 in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…Several previous studies showed that miR-378-3p was downregulated in CRC, esophageal squamous cell carcinoma and prostate cancer (27)(28)(29). In addition, miR-378-3p has been confirmed to be downregulated in CRC compared with adjacent normal colorectal tissues (28)(29)(30), consistent with the present study, and could serve as an independent prognostic marker or potential target of novel cancer therapies. The putative binding of miR-378-3p at the 3'UTR site of LBX2 further supports the hypothesis that miR-378-3p may be an upstream regulator of LBX2 in CRC.…”
Section: Discussionsupporting
confidence: 91%
“…Research shows that miR-124-3p expression inhibits cancers such like gastric [22] and bladder cancer [23], osteosarcoma [24], and glioma [25]. Previous investigations also validated that miR-124-3p expression is downregulated in PCa [26], suggesting that high expression of circ-TRPS1 promotes the progress of PCa by adsorption of miR-124-3p.…”
Section: Discussionmentioning
confidence: 89%
“…The CPT1 family constitutes the rate‐limiting step of FAO and comprises three different enzymes: CPT1A (which is present mostly in the liver), CPT1B (which is expressed mainly in the muscles), and CPT1C (mainly expressed in the brain). Overexpression of CPT1A has been shown to be associated with tumor progression in several cancer types such as breast cancer, prostate cancer, lymphoma, and leukemia . Similarly, others have shown that inhibition of this enzyme increases apoptosis and suppresses cancer cell proliferation, neovascularization, and chemoresistance .…”
Section: Multiple Myeloma and Fatty Acid Metabolismmentioning
confidence: 97%